Tinjauan Yuridis Tanggung Jawab Orang Tua terhadap Anak Pasca Perceraian - Muzakki, Muh Afif; Sodiqin, Ali; Qudussalam, Abdul; Murniati, Dewi (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2024)
Divorce cases in Indonesia are increasing, this has also resulted in many male parents (fathers) ignoring their responsibilities to their children. In connection with legal provisions, children must still receive their rights as children based on Article 45 paragraph 1 of Law no. 1 of 1974 concerning Marriage which states